La(III) Complex of Assymetrical Heptadentate (N4O3) Schiff Base - Izadkhah, Vida; Salehzadeh, Sadegh; Davoodi, Leila; Golbedaghi, Reza; Bayat, Mehdi (Asian Journal of Chemistry, 2010)
A systematic study on the performance of Pople-style basis functions such as 6-31G*, 3-21G* and LanL2MB on the molecular structure and highest occupied molecular orbital (HOMO) and lowest-unoccupied molecular orbital (LUMO) of a neutral complex of La(III) with ligand H3L, [La(L)], where L is of the complex of asymmetrical potentially heptadentate (N4O3) Schiff base ligand {N [(CH2)3N=CH(2-OH-5-BrC6H3)]- [(CH2)2N=CH(2-OH-5-BrC6H3)]2} have been carried out. The calculations were performed at both ab initio restricted Hartree-Fock (RHF) and DFT (B3LYP) methods. The calculations confirmed that this ligand can effectively encapsulates a lanthanide ion and enforce a seven-coordinate geometry. The results show that the calculated bond lengths and bond angles and also energy levels of this complex are considerably depend on both the method and basis set.